Factors contributing to non-utilization of primary health care services by community in the Greater Tzaneen Municipality, Mopani District - Masemola, Seepati Olga (My University, 2021)
Background: The utilization of primary health care (PHC) facilities has declined as most patients are using the hospitals for minor ailments. The study aimed to investigate factors that contribute to non-utilization of PHC services by the community in Greater Tzaneen Municipality, Mopani District, Limpopo Province. Methodology: quantitative research method was used, and data was collected using self-designed questionnaire. Total of 101 respondents out of 135 population participated in the study. Simple random sampling was used. The questionnaire was piloted to ensure reliability in a different setting. Data was analyzed using SPSS version 24. The outcome of the analysis was presented as frequencies and percentages in tables, pie charts and bar graphs. Ethical standards were adhered to throughout the study. Results: Demographic results indicated that the most of the respondents were females, aged between 26-35 years, speak the Sepedi language unemployed, went up to secondary school level using public transport, and have used their local clinic before more than. Many indicated that they have visited the hospital for reasons other than maternal and child health, chronic diseases and medication and minor illnesses. 25 factors recorded and the respondents reported six major factors that contributed to non-utilizing their PHC services. Factors included long queues and waiting times, no drugs and essential medication, PHC not operating for 24 hours and not operating for 7 days per week and nurses’ negative attitudes toward the community. Conclusions: Demographic results did not impact on the non-utilization of PHC services, but community-related, administrative factors and health-related factors contributed to non-utilization of PHC services
Thesis (M.A. (Nursing)) -- University of Limpopo, 2021
Keywords: Community; Factors; Non-utilization; PHC services; Primary health care; Community-based social services; Nursing